Sistem Pakar Penentuan Menu Makanan Sehat Penderita Penyakit Kolesterol Sesuai Golongan Darah Pasien Menggunakan Metode Forward Chaining Dan Backward Chaining - Millah, Rima Izzul; Tanuwijaya, Haryanto; Ayuningtyas, Ayuningtyas (Jurnal JSIKA, 2012)
Cholesterol is a fatty substance contained elements in the blood and can not be dissolved. causing factors of the high cholesterol is the process of aging, heredity and an unhealthy lifestyle. By setting a healthy diet based on blood type, cholesterol in the body will be controll. The use of Expert System for Determining Patient Menu Foods Healthy for Cholesterol Patients According to resolve the problem by consuming food according to blood type. Search method was used Backward Chaining and Forward Chaining. That expert systems have been created to provide information on the form that affects cholesterol levels and healthy diet according to blood group owned by the patient.”   Keywords : Expert System, Backward Chaining, Forward Chaining, Cholesterol, Blood Type.